Copper–cobalt thermoelectric generators: power improvement through optimized thickness and sandwiched planar structure - Selvan, Krishna Veni; Rehman, Tariq; Saleh, Tanveer; Mohamed Ali, Mohamed Sultan (IEEE, 2018)
In this paper, metallic thermoelectric generators were studied and fabricated using copper (Cu) and cobalt (Co) as their respective positive and negative thermoelements. Thus, the chosen Cu-clad polyimide substrate alleviated the deposition of Cu and eased the microfabrication. A lateral device structure might assist in generating larger output power through its longer thermoleg length. Hence, the fabricated thick-film devices had planar and lateral structures with lateral heat flow and lateral thermopile layout. The strong correlations of electrical and thermal conductivities in metal thermoelements have resulted in lower Seebeck coefficient along with reduced thermoelectric power-generating performances. Alternatively, a thermoleg cross-sectional area (A) optimization approach may optimize these disrupting correlations and improve their power-generating effectiveness,whereas a sandwichedplanar structure can allow more thermopiles to be integrated without influencing the generator’s size. Both A optimization and sandwiched planar structure have rarely been applied and studied in the past works and have never been implemented using metal thermoelements. Hereafter, a Cu–Co device was enhanced through A optimization by increasing the thickness of Co over 3.86 times the Cu thickness, and the implementations of a sandwiched planar structure. Herein, a flexible sandwiched planar thermoelectric generatorwas fabricated for the first time, using simpler microfabrication. This enhancedCu–Co generator achieved a thermoelectric efficiency factor of 6.6×10−3 μWcm−2K−2 (12.89 μWcm−2) at a temperature difference of 44.2 K. It remarked 3.1 times of improvement (by stacking three sets of thermopile) than its similar single Cu–Co thermopile of ten thermocouples.